Comprehensive omics studies of p53 mutants in human cancer. (9th July 2022) - Malhotra, Lakshay; Singh, Alankrita; Kaur, Punit; Ethayathulla, Abdul S
Abstract: The p53 is the master regulator of the cell known for regulating a large array of cellular processes. Inactivation of p53 by missense mutations is one of the leading causes of cancer. Some of these mutations endow p53 with selective oncogenic functions to promote tumor progression. Due to the vast array of mutations found in p53, the experimental studies showing the role of different mutant p53 as an oncogene are also expanding. In this review, we discuss the oncogenic roles of different p53 mutants at the cellular level identified by multi-omics tools. We discuss some of the therapeutic studies to tackle p53 mutants and their downstream targets identified by omics. We also highlight the future prospective and scope of further studies of downstream p53 targets by omics.